An instant preparation method for nucleic acids of filamentous fungi - Jurgen Wendland; Klaus B. Lengeler; Erika Kothe (Fungal Genetics Reports, 1996)
Preparation methods for both DNA and RNA of filamentous fungi often are labour intensive and unreliable. The rapid preparation protocol presented here has been found to work for Schizophyllum commune and other filamentous fungi.